Evolution of groundwater fluoride in land subsidence areas after groundwater cessation: A case study at Cangzhou - Danyang Sun; Hexue Li; Qiang Liu; Junxia Li (地质科技通报, 2023)
Objective The South-to-North Water Transfer Project (SNWTP) has improved water use in northern China and further reduced deep groundwater extraction in the North China Plain. However, its impact on the evolution of regional groundwater hydrochemistry is still unknown. Methods In this paper, Cangzhou, which has experienced severe land subsidence due to groundwater overexploitation and has received water resources from the SNWTP since 2015, was selected as the study area to investigate the effects of the SNWTP on groundwater chemistry. In 2017 and 2021, groundwater samples from Ⅲ and Ⅳ confined aquifers were collected to determine the hydrochemical characteristics. Moreover, the average annual land subsidence of the regional layer was further evaluated by using SBAS-InSAR to identify the correlation between variations in land deformation and changes in groundwater chemistry. Results The results showed that in comparison with those before the SNWTP, the groundwater fluoride concentration was slightly decreased,